Remittances and the macroeconomy: The case of small island developing states - Catalina Amuedo-Dorantes; Susan Pozo; Carlos Vargas-Silva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
In this paper we examine how remittances relate to the exchange rate, natural disasters and foreign aid in developing economies. By using panel VAR methods we are able to compensate for both data limitations and endogeneity among variables. We find that while foreign aid tends to appreciate the real exchange rate, remittances do not have the same impact. We also detect an inverse relationship between the real exchange rate and remittance amounts, with real exchange rate depreciation increasing remittance inflows. Of particular interest is the observation that the small island developing states subsample of countries behave differently from the full sample of developing countries in a number of ways. Of note is the differing impact of disaster shocks on the real exchange rate and on the level of remittances across the two samples.
Keywords: F24; O19; 330; remittances; natural disasters; small island developing states; migration; Rücküberweisung (Migranten); Wechselkurs; Naturkatastrophe; Entwicklungshilfe; Entwicklungsländer; Insel; Kleines-Land-Modell